Emission behaviour of vegetable oil fuel compatible tractors fuelled with different pure vegetable oils. (1st March 2016) - Emberger, Peter; Hebecker, Dietrich; Pickel, Peter; Remmele, Edgar; Thuneke, Klaus
Highlights: Eight vegetable oils and one mixture were tested in two vegetable oil compatible engines. Vegetable oils differed in their emission behaviour dependent on the engine operation mode. Increasing unsaturation of the oils led to higher NO X emission at medium and high torque. Increasing unsaturation of the oils led to higher emissions of CO, HC and PM at idle mode. Abstract: The emission behaviour of pure vegetable oils to be used as a fuel was researched using two vegetable oil fuel compatible tractors. The tractor engines were equipped with a common-rail and pump-line injection system. For the research eight different vegetable oils, one vegetable oil mixture and diesel fuel were used. Vegetable oils are basically triacylglycerides and can be characterised by the two structure indices average number of carbon atoms (AC) and average number of double bonds (ADB). The results show that both tractors can be operated with vegetable oils and diesel fuel at about the same level of efficiency. Specific test cycle emissions of nitrogen oxides (NO X ) tend to be higher while specific carbon monoxide (CO), hydrocarbon (HC) and particle mass (PM) emissions tend to be lower with the vegetable oils compared to diesel fuel.The emission behaviour of the two tractors was influenced by the type of vegetable oil used. The differences were dependent on the operation mode. At average and high load operation points the emissions of CO, HC and PM were at the same level, whereas the NO X emissions were rising with increasing ADB of the vegetable oils. At low load and idle operation the emissions of CO, HC and PM were rising with increasing unsaturation respectively increasing ADB of the vegetable oils. The observed increase of NO X at average and high load could not be recognized anymore at low load and idle and is even reversed for one tractor. This indicates deteriorated combustion with increasing unsaturation of the vegetable oils at idle and low load.